ANALISIS RASIO KEUANGAN DAN STRUKTUR KEPEMILIKAN PERUSAHAAN DALAM MEMPREDIKSI KESULITAN KEUANGAN: SEBUAH RISET EMPIRIS PADA PERUSAHAAN NONKEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hizkia Bhisma Nararya Yudadibrata; Yanuar Nanok Soenarno (Universitas Katolik Indonesia Atma Jaya, 2016)
The financial crisis in Asia that hit Indonesia in 1997-1998 caused research related to the predictions of financial difficulties mostly done. This study aims to examine whether financial ratios (which include liquidity ratios, activity, leverage, profitability, and markets) and corporate ownership structures (institutional ownership and managerial ownership) can be used in predicting possible financial difficulties. The statistic used in this research hypothesis test is logistic regression test. Companies that include the population are nonfinancial corporations that have financial difficulties and companies that have a healthy financial condition in the period 2010. Sample size used in this study amounted to 105 companies: 51 companies experiencing financial difficulties and 54 healthy companies. This study uses three years of observation period of research, ie year 2007-2009, to see whether the variables can predict financial difficulties that occurred in 2010. The results showed that the ratio of liquidity, activity, leverage, and profitability ratio can predict the possibility of financial difficulties.